2011
DOI: 10.1177/1753425911411595
|View full text |Cite
|
Sign up to set email alerts
|

A novel post-exposure medical countermeasure L-97-1 improves survival and acute lung injury following intratracheal infection with Yersinia pestis

Abstract: Yersinia pestis, a Gram-negative bacillus causing plague and Centers for Disease Control and Prevention (CDC) classified Category A pathogen, has high potential as a bioweapon. Lipopolysaccharide, a virulence factor for Y. pestis, binds to and activates A1 adenosine receptor (AR)s and, in animals, A1AR antagonists block induced acute lung injury (ALI) and increase survival following cecal ligation and perforation. In this study, rats were infected intratracheally with viable Y. pestis [CO99 (pCD1+/Δpgm) 1 × 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The same study indicated that pretreatment of A1AR agonist, 2’Me-2-chloro-N6-cyclopentyladenosine, attenuates PMN recruitment and microvascular permeability. On the other hand, post-infection treatment of a combination of A1AR antagonist L-97-1 and ciprofloxacin improves the outcome of Y. pestis infection in rats, indicating a protective effect of A1AR ( 139 ). Furthermore, A1AR knockout mice show significantly increased macrophage and neutrophil infiltration in the airway after influenza A/WSN/33 (H1N1) infection when compared to wild-type counterparts and daily treatment of A1AR antagonist 8-cyclopentyl-1,3-dipropylxanthine results in improved outcome ( 140 ).…”
Section: Adenosine At the Interphase Of Hypoxia And Inflammation In Lmentioning
confidence: 99%
“…The same study indicated that pretreatment of A1AR agonist, 2’Me-2-chloro-N6-cyclopentyladenosine, attenuates PMN recruitment and microvascular permeability. On the other hand, post-infection treatment of a combination of A1AR antagonist L-97-1 and ciprofloxacin improves the outcome of Y. pestis infection in rats, indicating a protective effect of A1AR ( 139 ). Furthermore, A1AR knockout mice show significantly increased macrophage and neutrophil infiltration in the airway after influenza A/WSN/33 (H1N1) infection when compared to wild-type counterparts and daily treatment of A1AR antagonist 8-cyclopentyl-1,3-dipropylxanthine results in improved outcome ( 140 ).…”
Section: Adenosine At the Interphase Of Hypoxia And Inflammation In Lmentioning
confidence: 99%
“…Previously it was reported that when administered in combination with antibiotics as a 72 h delayed treatment, L-97-1 improved survival and acute lung injury in a rat model of Y. pestis induced pneumonic plague and sepsis (Wilson, et al, 2011). Moreover, it was reported that adenosine A 1 receptor antagonists block endotoxin induced acute lung injury and the release of thromboxane and IL-6 from human pulmonary artery endothelial cells (Neely et al, 1997; Wilson and Batra, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…I n vitro studies in humans and in vivo studies in animals suggest that activation of adenosine A 1 receptors may contribute to the pathophysiology of acute lung injury and renal failure of sepsis (Knight, et al., 1993; Neely et al, 1997; Wilson and Batra, 2002; Wilson et al, 2011). In the lung, activation of adenosine A 1 receptors on endothelial cells increases their permeability, while their activation on alveolar type 2 cells decreases lung fluid clearance, actions on both cell types that promote pulmonary edema (Factor et al, 2007; Neely and Keith, 1995; Neely et al., 1997; Satoh et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations